A Thorough Study on the Photoisomerization of Ferulic Acid Derivatives. Issue 11 (15th March 2021) - Moni, Lisa; Banfi, Luca; Basso, Andrea; Mori, Alessia; Risso, Federica; Riva, Renata; Lambruschini, Chiara
Abstract: A thorough study on the ( E ) to ( Z ) photoisomerization of ferulic acid derivatives (esters, amides of all types, and ketones) was carried out. At the photostationary state, only aliphatic or benzylic tertiary amides reach a nearly complete conversion of ( E ) isomers into the ( Z ) ones, whereas for esters, primary and secondary amides or aromatic tertiary amides mixtures of ( Z )/( E ) ranging from 7 : 93 to 72 : 28 are observed. Ketones show rather limited photoisomerization. However, ( Z ) ketones may be obtained by the reaction of organometal compounds with an isomerized ( Z ) Weinreb amide. Abstract : A comprehensive study of photoisomerzation of ferulic acid derived esters, amides, and ketones was carried out. Only in the case of aliphatic tertiary amides, a nearly complete E→Z conversion was achieved.